Renewable motor fuels : the past, the present, and the uncertain future - Brownstein, Arthur M. (Butterworth-Heinemann, 2015)
This book presents an opportunity to gain an insightful understanding of all the key aspects of alternative automotive fuels in one book. Brownstein describes various sources of renewable motor fuels (including ethanol, algae, isobutanol, natural gas, and battery power) and their production processes, specific properties, and economic advantages/disadvantages. This comprehensive coverage of such an important topic is crucial for anyone with an interest in renewable fuels, from researchers to engineers to end-users. It presents a clear overview on a variety of renewable motor fuel technologies, balancing history, technology, and policy; provides the status of current and developing renewable motor fuel technologies and their uses worldwide; discusses the competitive economics of renewable fuel processes and their respective market interactions. --